2006
DOI: 10.1002/adfm.200500841
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial‐Layer Atomic Layer Deposition for Fabrication of Non‐Close‐Packed Inverse‐Opal Photonic Crystals

Abstract: A method is presented for predicting and precisely controlling the structure of photonic crystals fabricated using sacrificial‐layer atomic layer deposition. This technique provides a reliable method for fabrication of high‐quality non‐close‐packed inverse shell opals with large static tunability and precise structural control. By using a sacrificial layer during opal infiltration, the inverse‐opal pore size can be increased with sub‐nanometer resolution and without distorting the lattice to allow for a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 26 publications
(36 reference statements)
6
57
0
Order By: Relevance
“…Unlike CVD, ALD is self-limiting by keeping the precursors separate, enabling ultrahigh-precision control over the deposition and providing superior film conformity and uniformity even for complex structures with ultrahigh aspect ratios [15][16][17][18][19]. Thus, ALD has been used as a way of infiltrating NCC templates to generate inverse opals [19][20][21][22][23][24][25][26]. Our previous studies [27,28] demonstrated that ALD can be used to significantly reinforce films composed of randomly packed polydisperse nanoparticles.…”
Section: Introductionmentioning
confidence: 95%
“…Unlike CVD, ALD is self-limiting by keeping the precursors separate, enabling ultrahigh-precision control over the deposition and providing superior film conformity and uniformity even for complex structures with ultrahigh aspect ratios [15][16][17][18][19]. Thus, ALD has been used as a way of infiltrating NCC templates to generate inverse opals [19][20][21][22][23][24][25][26]. Our previous studies [27,28] demonstrated that ALD can be used to significantly reinforce films composed of randomly packed polydisperse nanoparticles.…”
Section: Introductionmentioning
confidence: 95%
“…2 indicates. Finally, this backbone template can be further modified by conformally coating dielectric layers onto its interior, as reported by Míguez et al, King et al,and Graugnard et al,31,45,46 and shown in Fig. 2͑e͒.…”
Section: Introductionmentioning
confidence: 86%
“…46 With this technique, structural modifications to the original template and inverse shell opal backbone can be made with precise and independent control of the tube and sphere radii, adding additional geometrical flexibility and PBG adjustment. In this technique ͑Fig.…”
Section: Introductionmentioning
confidence: 99%
“…With ALD, highly conformal films can be grown with a precision of 0.05 nm, which, when combined with the availability of a wide range of low temperature film growth protocols, enables a high degree of control over material and structural properties to precisely tune optical properties [3]. Two-dimensional photonic crystals have been developed extensively for applications in optical interconnects, beam steering, and sensor devices; and are predominantly fabricated by electron-beam lithography.…”
Section: School Of Materials Science and Engineering Georgia Institute mentioning
confidence: 99%